My promised land [compact disc, unabridged] : the triumph and tragedy of Israel - Shavit, Ari (Random House Audio : Books on Tape, 2013)
Tells the story of Israel as it has never been told before. Facing unprecedented internal and external pressures, Israel today is at a moment of existential crisis. Through revealing stories of significant events and of ordinary individuals, pioneers, immigrants, entrepreneurs, scientists, army generals, peaceniks, settlers, and Palestinians, Israeli journalist Ari Shavit illuminates many of the pivotal moments of the Zionist century that led Israel to where it is today.